2019
DOI: 10.7600/jpfsm.8.137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different stretch amplitudes of dynamic stretching on joint range of motion

Abstract: This study examined the effects of different dynamic stretching (DS) amplitudes on joint range of motion (ROM), passive torque (PT), and subjective fatigue. Twelve healthy subjects (age [mean ± SD] = 19.3 ± 1.0 years) underwent three experimental trials: DS at maximal active ankle plantarflexion-dorsiflexion ROM (DS100), DS at 80% maximal active ROM (DS80), or control. Ankle angle and PT were measured before and after DS with the ankle passively dorsiflexed at 1º/s to its maximal ROM. DS consisted of four sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…The present findings demonstrated that ankle ROM was increased after both DS velocities (approximately 1.0° increment after DS100, and approximately 2.1° increment after DS50). The increase in ankle ROM after DS50 was similar to that reported in previous studies (10,11,14,18), whereas the increase after DS100 was less than that reported in previous studies. However, because there was no significant difference in the increase in ROM between trials, the results indicated that there was no effect of DS velocity on increase in ankle ROM.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The present findings demonstrated that ankle ROM was increased after both DS velocities (approximately 1.0° increment after DS100, and approximately 2.1° increment after DS50). The increase in ankle ROM after DS50 was similar to that reported in previous studies (10,11,14,18), whereas the increase after DS100 was less than that reported in previous studies. However, because there was no significant difference in the increase in ROM between trials, the results indicated that there was no effect of DS velocity on increase in ankle ROM.…”
Section: Discussionsupporting
confidence: 90%
“…This increment in subjective fatigue was due to the increment of DS velocity. Thus, DS velocity seems to be one of the factors increasing DS-induced fatigue, similar to DS duration and DS amplitude (11,20). Impairment of exercise performance by DS-induced fatigue is a serious problem (18,20).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The test–retest reliability for maximal dorsiflexion angle, displacement of the MTJ at the maximal dorsiflexion angle, and passive torque at maximal dorsiflexion angle were reported in previous studies [ 15 , 21 ].…”
Section: Methodsmentioning
confidence: 56%